Low Occurrence of Pathogenic Yersinia enterocolitica in Clinical, Food, and Environmental Samples: a Methodological Problem - Fredriksson-Ahomaa, Maria (American Society for Microbiology, 2003)
While Yersinia enterocolitica is an important pathogen, which can cause yersiniosis in humans and animals, its epidemiology remains obscure. The pig is the major reservoir of pathogenic Y. enterocolitica of bioserotype 4/O:3, the most common type found in humans. Y. enterocolitica is thought to be a significant food-borne pathogen, although pathogenic isolates have seldom been recovered from foods. The low isolation rate of this pathogenic bacterium in natural samples, including clinical, food, and environmental samples, may be due to the limited sensitivity of culture methods. During the last decade, numerous DNA-based methods, such as PCR and colony hybridization assays, have been designed to detect pathogenic Y. enterocolitica in natural samples more rapidly and with better sensitivity than can be achieved by culture methods. In addition, the occurrence of pathogenic Y. enterocolitica in natural samples is clearly higher with PCR than with culture methods. The methods available for detection of pathogenic Y. enterocolitica in natural samples are reviewed in this article.